2019
DOI: 10.1016/j.jval.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and Coverage With Evidence Development: Does Practice Meet Theory?

Abstract: In theory, a successful coverage with evidence development (CED) scheme is one that addresses the most important uncertainties in a given assessment. We investigated the following: (1) which uncertainties were present during the initial assessment of 3 Dutch CED cases, (2) how these uncertainties were integrated in the initial assessments, (3) whether CED research plans included the identified uncertainties, and (4) issues with managing uncertainty in CED research and ways forward from these issues.Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…However, a recent OECD report found that, to date, most performance-based MEAs have failed to decrease clinical uncertainty (Morel et al, 2013;Wenzl and Chapman 2019). This results, among other reasons, from the fact that CED protocols generally fail to address the majority of the uncertainties which were initially identified (Pouwels et al, 2019). The authors further suggest that jurisdictions implement legislation that (at least to some extent) allows them to share information on effectiveness between countries, an idea that seems particularly relevant to rare diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent OECD report found that, to date, most performance-based MEAs have failed to decrease clinical uncertainty (Morel et al, 2013;Wenzl and Chapman 2019). This results, among other reasons, from the fact that CED protocols generally fail to address the majority of the uncertainties which were initially identified (Pouwels et al, 2019). The authors further suggest that jurisdictions implement legislation that (at least to some extent) allows them to share information on effectiveness between countries, an idea that seems particularly relevant to rare diseases.…”
Section: Discussionmentioning
confidence: 99%
“…They may also be sceptical about the robustness of the findings of VOI with the associated modelling and assumptions. Nevertheless, incorporating this approach into decision frameworks is intuitive if it is introduced as a decision support tool to reduce the chance and costly consequences of sub-optimal decisions [ 1 , 2 , 29 ]. Many decision-making organisations embrace evidence-based approaches in making decisions using cost-effectiveness analysis; furthermore, handling and presenting uncertainty is already embedded in the current decision frameworks in many jurisdictions.…”
Section: The Way Forwardmentioning
confidence: 99%
“…3 In the Netherlands, conditional reimbursement schemes with evidence collection are hardly based on uncertainties other than imprecision. 12 With use of exploratory modeling, one could explore under which circumstances (eg, at which survival rate, or in case of which parallel developments in the control of the relevant disease condition) ipilimumab is cost-effective. An adaptive strategy can then be implemented where evidence is collected and clear thresholds are set: if a certain threshold (eg, survival rate) is reached, reimbursement of the drug can be continued, if not, reimbursement should be withdrawn.…”
Section: Dealing With Uncertaintymentioning
confidence: 99%